2009
DOI: 10.1111/j.1442-9071.2009.02081.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the anterior segment in glaucoma

Abstract: Although constituting only about a quarter of all glaucoma, angle closure glaucoma causes a disproportionate amount of visual morbidity and is predicted to be responsible for almost half of bilateral blindness by 2020. Early detection and treatment of angle closure significantly improves visual prognosis. Identification of eyes at risk of angle closure currently relies on opportunistic case detection, often by gonioscopy. However, gonioscopy is a highly subjective technique and often leads to misdiagnosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
0
33
0
6
Order By: Relevance
“…A recent study suggested that gonioscopy should be still considered the goldstandard method in detecting PAC and it cannot be replaced by the anterior segment imaging even if both AS-OCT and UBM can be useful in several circumstances (Barkana et al, 2007;Dorairaj et al, 2012;Friedman et al, 2012;Ishikawa et al, 2000;McKee et al, 2013;Pavlin et al, 1992;Pekmezci et al, 2009;Quek et al, 2011;See, 2009). …”
Section: Anterior Segment Imagingmentioning
confidence: 95%
“…A recent study suggested that gonioscopy should be still considered the goldstandard method in detecting PAC and it cannot be replaced by the anterior segment imaging even if both AS-OCT and UBM can be useful in several circumstances (Barkana et al, 2007;Dorairaj et al, 2012;Friedman et al, 2012;Ishikawa et al, 2000;McKee et al, 2013;Pavlin et al, 1992;Pekmezci et al, 2009;Quek et al, 2011;See, 2009). …”
Section: Anterior Segment Imagingmentioning
confidence: 95%
“…found no statistical difference between the results of two examiners: the 95% intra-observer limits of agreement were within ±5°, with ICC (intra-class correlation coefficient) below 0.75. The EAS-1000 shows also good intra-observer repeatability, with a 95% inter-observer limits of agreement within ±6° and an ICC around 0.75 in healthy subjects [109]. The Pentacam seems to have the same intra-observer repeatability, with relative repeatability of 5.68% for volume, 3.07% for depth and 14.41% for angle [111].…”
Section: Scheimpflug Photographymentioning
confidence: 67%
“…Anterior chamber depth can be measured locating manually the surface of the posterior cornea and the anterior surface of crystalline lens [103,109].…”
Section: Scheimpflug Photographymentioning
confidence: 99%
“…Ayr›ca görülebilir ›fl›k kulland›¤›ndan miyozisi uyarmakta ve aç›n›n oldu¤undan genifl görünmesine yol açabilmek-tedir (12).…”
Section: Tart›flmaunclassified